Biological repair of the degenerated intervertebral disc by the injection of growth factors - Masuda, Koichi (Springer-Verlag, 2008)
The homeostasis of intervertebral disc (IVD) tissues is accomplished through a complex and precise coordination of a variety of substances, including cytokines, growth factors, enzymes and enzyme inhibitors. Recent biological therapeutic strategies for disc degeneration have included attempts to up-regulate the production of key matrix proteins or to down-regulate the catabolic events induced by pro-inflammatory cytokines. Several approaches to deliver these therapeutic biologic agents have been proposed and tested in a preclinical setting. One of the most advanced biological therapeutic approaches to regenerate or repair a degenerated disc is the injection of a recombinant growth factor. Abundant evidence for the efficacy of growth factor injection therapy for the treatment of IVD degeneration can be found in preclinical animal studies. Recent data obtained from animal studies on changes in cytokine expression following growth factor injection illustrate the great potential for patients with chronic discogenic low back pain. The first clinical trial for growth factor injection has been initiated and the results of that study may prove the usefulness of growth factor injection for treating the symptoms of patients with degenerative disc diseases. The focus of this review article is the effects of an in vivo injection of growth factors on the biological repair of the degenerated intervertebral disc in animal models. The effects of growth factor injection on the symptoms of patients with low back pain, the therapeutic target of growth factor injection and the limitations of the efficacy of growth factor therapy are also reviewed. Further quantitative studies on the effect of growth factor injection on pain generation and the long term effects on the endplate and cell survival after an injection using large animals are needed. An international academic-industrial consortium addressing these aims, such as was achieved for osteoarthritis (The Osteoarthritis Initiative), may further the development of biological therapies for degenerative disc diseases.